Desenvolvimento de um sistema de geração de bolhas para estudos de escoamento bifásico - Wojcik, Mariane (2019)
Reduced size bubbles are applied in various industrial processes, in particular involving oil extraction, transport and refining operations. Petroleum is a viscous oil used worldwide, widely used in various applications, generating several studies in its productive stages, as in the two phase flow part. The main presentation of the twophase flow contrasts with the liquid-gas form, where air bubbles appear in various shapes and sizes. These bubbles tend to influence the mode and quality of viscous liquid flow. Another part of the oil production process with wide applicability of micro size bubbles is the extraction of oil. In this primary stage of production, there is a marked formation of water from the well injection process. This water is even necessary for the process of removing oil from the ground, however, after extraction is necessary the separation of oil from water. There are several techniques used to separate these two fluids. One of the most used is flotation, which consists of the adherence of microbubbles in the oil particles, allowing their flotation and consequent separation of oil from water. The NUEM – Multiphase Flow Research Center, located at the Federal University of Technology – Paraná, develops several researches promoted in the use of microbubbles in order to improve the efficiency in the exploration and production of the oil. In the commercial environment, there is equipment aimed at producing controllable microbubbles, however they have a high acquisition value and demand import bureaucracies. In this context, the present work is aimed at designing, manufacturing and assembling a functional prototype of a controllable size bubble generation system, controlled by software developed in a segment-specific programming platform. Subsequent to the development of the equipment, several experimental tests are performed using a high rate image acquisition camera. For the processing of the capture images, a logic code is developed in the Matlab numerical calculation software, whereby subsequent extraction of data related to the generated bubbles occurs. The results obtained are analyzed considering the size of the bubbles generated and the most ideal parameters for the formation of microbubbles in order to measure the effectiveness of the equipment.